Social network analysis of self-taught e-learning communities - Zaphiris, Panayiotis; Laghos, Andrew (My University, 2007)
The technique of Social Network Analysis (SNA) has been for years used extensively in the fields of sociology and communication research. Recently however, SNA has been extended to study online communication and virtual communities. In this paper, we have used SNA to analyse the social networks that have formed around a self-taught e-learning community. In traditional face-to-face learning environments, the students are part of a classroom where there is a teacher who presents the lectures and supervises the communication interactions. But what happens when the learning takes place online and there is no teacher to mentor the process? We have carried out SNA on such a community with the aim of discovering what roles, groups and characteristics the students take on when there is no teacher present and discuss the implications of our results.
Keywords: Social networks; Online communities; Computer-mediated communication; Social network analysis; SNA; Knowledge; Social interaction; Learning environments; Centrality; Cliques; Cohesion; Cooperative learning; Collaborative learning; Virtual communities; Web based communities; E-learning; Online learning; Self-taught communities